Kepemimpinan dan Motivasi : Tinjauan Literatur tentang Pengaruhnya terhadap Kinerja Karyawan - Susan Febriantina; Jonathan Nofaomasi Daeli; Khalizah Alfi Fadhliyah; Ulayya Antania Hanjani; Zahra Aisha Febrila (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to identify factors that significantly influence employee performance and formulate strategies to improve it. This research was conducted through a comprehensive literature study of various studies related to employee performance. The main focus of this research is on internal factors such as motivation, leadership, and organizational culture, as well as external factors such as technology and changes in the business environment. The research results show that employee performance is influenced by various interrelated factors. Motivation, both intrinsic and extrinsic, is a key factor that encourages employees to achieve optimal performance. Effective leadership, especially transformational and democratic leadership styles, also has an important role in improving performance. In addition, a positive organizational culture, conducive work environment, and appropriate use of technology can increase employee productivity and job satisfaction. To improve employee performance, organizations need to create a supportive and motivating work environment. This can be done by implementing various strategies, such as providing ongoing training and development, implementing a fair and transparent compensation system, building positive interpersonal relationships, and providing sufficient autonomy to employees. Apart from that, organizations also need to pay attention to external factors such as technological changes and evolving market dynamics.